2014
DOI: 10.1177/1934578x1400901111
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Analysis, Antioxidant and Anti-Inflammatory Activity of Calyces from Physalis peruviana

Abstract: Physalis peruviana calyces are used extensively in folk medicine. The crude ethanolic extract and some fractions of calyces were evaluated in order to explore antioxidant and anti-inflammatory activities. The anti-inflammatory activity was evaluated by the TPA-induced ear edema model. The antioxidant in vitro activity was measured by means of the superoxide and nitric oxide scavenging activity of the extracts and fractions. The butanolic fraction was found to be promising due to its anti-inflammatory and antio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 14 publications
1
22
0
3
Order By: Relevance
“…BF was concentrated to dryness under vacuum at 40 °C . Previous works of our group identified rutin as the main of two compounds elucidated in HEE and BF (NMR and MS spectroscopy) . For this research, the content of rutin in both preparation was confirmed by a previously validated HPLC‐UV method.…”
Section: Methodsmentioning
confidence: 54%
See 1 more Smart Citation
“…BF was concentrated to dryness under vacuum at 40 °C . Previous works of our group identified rutin as the main of two compounds elucidated in HEE and BF (NMR and MS spectroscopy) . For this research, the content of rutin in both preparation was confirmed by a previously validated HPLC‐UV method.…”
Section: Methodsmentioning
confidence: 54%
“…Recently, our research group described the antioxidant, anti‐inflammatory and hypoglycaemic activity for HEE and for its butanol fraction (BF). Therefore, in view of the promising pharmacological effects of HEE and BF, the solubility and permeability issues of its main secondary metabolite (rutin), and the probable influence of the whole chemical composition of extract and fraction on these properties, this work aimed to evaluate the matrix effects of HEE and BF on the biopharmaceutics classification of rutin.…”
Section: Introductionmentioning
confidence: 99%
“…For this determination, 5 g of material was weighed and placed through a funnel positioned at a fixed height on a graph paper flat horizontal surface and allowing this form a cone, measuring the height (h) and radius (r). The tangent of the angle of repose is given by the expression h/r ratio [8]. Five repetitions were done in triplicate for a total of fifteen data.…”
Section: Angle Of Reposementioning
confidence: 99%
“…The hygroscopicity showed values between 8.84 % and 15.61 %. Experiments 3,4,7,8,11,12,15 and 16 were the particles with the higher proportion of colloidal silicon dioxide that showed the lowest hygroscopicity and this was the factor with the main influence in this variable (Factor F) (table 3). For high concentrations of colloidal silicon dioxide, the extract could be trapped within these solid particles and then it could be almost unavailable for water adsorption [44].…”
Section: Hygroscopicitymentioning
confidence: 99%
See 1 more Smart Citation